Sovereign Risk, Elections, and Contagion - Chi Li; Christopher Balding; Minsoo Lee (Asian Development Bank (ADB), 2013)
This paper aims to quantify the political risk effect and its different economic implications in normal and crisis situations through the proxy analysis of election and the sovereign bond spreads. Our study leads to three main findings. First, in normal economic situations, elections and government turnovers expand bond spreads, demonstrating investors' concern over the possibility of government policies or instability brought by the election. During a crisis, however, investors prefer change, indicating hope in new policies ameliorate public finances. Second, due to the prolonged eurozone sovereign debt crisis, elections in European countries have stronger contagion effects in their own region during a global slowdown period than a normal period. However, their effect does not carry over globally after the 2008 financial crisis. Third, results show that the election induced peak shrinks from 3 months before and after the election date to 1–2 months when the economic situation turns from normal to a downgraded period.
hdl:11540/2320
Keywords: F34; F36; O52; 330; election; sovereign bond; contagion; financial crisis; Europe; Asia